VARIABILITAS KARAKTERISTIK BIOLOGI TANAH PADA LAHAN KERING SUBOPTIMAL - Fahrizal Hazra; Latief Mahir Rachman (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Prominent problems in suboptimal land are often only related to the chemical and physical properties of the soil such as low soil pH, available nutrients and the ability of the soil to supply available water. Assessment of soil biological characteristics is needed to look at soil problems on dry land more comprehensively. The purpose of this study was to conduct a preliminary study of the variability of soil biological characteristics in suboptimal dry land. This study was carried out with a field survey accompanied by soil sampling using a composite method in 24 land locations which are the centers of development of the Department of Agriculture commodity development in five districts in Central Java Province that were randomly selected. In addition to soil organic matter, soil biological characteristic studied was the total number of soil microorganisms. The results of the study on both potato and sweet potato commodity lands showed there were intervals of the number of soil microorganisms, namely 1.83 x 105 - 1.63 x 106 CFU g-1 of soil and 3.90 x 105 - 1.10 x 106 CFU g-1 of soil. While the interval of soil respiration value is 4.80 - 10.97 mg C-CO2 kg-1 of soil day-1 for potato commodity land and 5.31 - 10.80 mg C-CO2 kg-1 of soil day-1 for sweet potato land. There was no strong correlation between the number of soil microorganisms and soil respiration, which was indicated by a correlation value of 0.29. The biological characteristics of the soil varied greatly, and they did not affect the type of commodity or location.